An Analysis of Jazz Composition: Waltz For Nile - Tunboot, Teerawat (Rangsit Music Journal, 2022)
This creative article focusing on analysis of jazz compositions Waltz For Nile a contrafact from Black Nile, the original composition of Wayne Shorter. To create the different of color and feel from Black Nile, the composer change time signature to 3/4, perform in jazz waltz style, change song form to A B A’, reharmonization, adding measure, tempo changes and switch time signature to 4/4 on saxophone ad lib part.